LITERATURE REVIEW: THE RELATIONSHIP BETWEEN STRESS AND EMOTIONAL EATING AMONG UNIVERSITY STUDENTS IN INDONESIA - Citta Nabila Rafida Putri; Ayik Mirayanti Mandagi (Journal of Community Mental Health and Public Policy)
Background: The prevalence of emotional mental disorders in adulthood has been increasing annually, with stress identified as a significant risk factor. Purpose: This study aims to investigate the correlation between stress and emotional eating among Indonesian university students. Methods: A systematic literature review was conducted using the PRISMA-P framework, analyzing relevant international and national articles from the Google Scholar database. Results: College students who experience stress have been shown to engage in emotional eating. Furthermore, emotional eating has been demonstrated to heighten the probability of obesity. Conclusion: The study confirms a significant correlation between stress levels and emotional eating behaviors among college students.